(untitled) (REMUNOM, 2026)
At the outset of this research, it is important to highlight that the dichotomy between public and private law was a prominent element in the legal tradition until the end of the 20th century. However, from the 1980s onwards, due to state indebtedness and the increased demand for more effective public services, legal instruments began to be developed that enabled joint action between the State and the private sector. Public-Private Partnerships (PPPs), established in the national legal system through Law No. 11,079 of December 30, 2004, constitute an important instrument to enable cooperation between public entities and the private sector, especially given the budgetary limitations faced by the State. The research question is: what elements of Public-Private Partnerships (PPPs) can be used as instruments for implementing public health policies in Brazil? The objective of this article is to analyze whether PPPs (Public-Private Partnerships) can be considered adequate tools to promote efficient and effective public health policies in Brazil, contributing to the realization of social rights foreseen in the 1988 Constitution. The research is exploratory, qualitative, and inductive in nature, operationalized through bibliographic and documentary research, and using the case study methodology, developed at the Hospital do Subúrbio, a PPP contract signed by the State of Bahia. The main results obtained indicate that PPPs can be used broadly and satisfactorily as tools to enable health services in the country, confirming the research hypothesis.